Identification of characteristics and incidence of injuries in Pencak Silat athletes in the adult competition category in East Java - Bahari, Dinda Farida Putri; Rahayuni, Kurniati (Indonesian Journal of Research in Physical Education, Sport, and Health, 2025)
Background: Pencak silat, as a competitive sport, has a high risk of injury. However, data on its characteristics and causative factors during pre-match and matches in East Java are still limited. Objective: This study aims to identify the characteristics and incidence of injuries in adult sparring category pencak silat athletes in East Java during training and matches. Methods: Using a quantitative descriptive method with a cross-sectional survey approach. Data were collected through a survey distributed to 100 athletes (61 men and 31 women) aged 17-22 years from 11 cities/districts in East Java, including information on injury characteristics and causal factors. Result: The results showed that the most dominant injuries that occurred during pre-match were blisters on the fingers (32%), bruises on the arms (38%), sprains on the lower legs (26%), and sprains on the ankles (33%), the leading causes were technical errors, lack of warm-up, and lack of facilities and infrastructure. During matches, the most common injuries were lower limb bruises (48%), ankle sprains (29%), and head/face abrasions (12%), which were caused by punching power, technical errors, and takedowns. While serious injuries such as dislocations and fractures had a low percentage, they had a significant impact on the athletes' performance. Conclusion: Overall, the findings suggest that the lower extremities are more susceptible to injury. The types of injuries varied, ranging from minor to severe. Initial treatment for minor injuries typically involves the RICE (Rest, Ice, Compression, Elevation) method, whereas severe injuries require further medical attention to prevent serious complications.